Dari Bantuan ke Kemandirian: Efektivitas Zakat Produktif dan Pendampingan dalam Meningkatkan Kesejahteraan Mustahiq - Noka, Isara Abda; Wardiana, Hesti; Ibnu, Ibnu (ITB AAS INDONESIA Surakarta, 2025)
This study aims to analyze the influence of productive zakat utilization and mentoring on the welfare of mustahiq (zakat recipients) at the Baitul Mal of Bener Meriah Regency. Productive zakat is viewed as an important instrument for promoting the economic independence of recipients, while mentoring is expected to strengthen their managerial capacity and business sustainability. This research employs a quantitative descriptive approach with a population of 100 mustahiq and a sample of 50 respondents selected through a simple random sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression with the assistance of SPSS version 18. The results show that productive zakat utilization has a positive and significant effect on the welfare of mustahiq (t-count 4.104 > t-table 2.014), whereas mentoring has no significant effect (t-count 1.136 < t-table 2.014). However, both variables simultaneously have a significant influence on mustahiq welfare (F-count 9.378 > F-table 2.802) with a coefficient of determination of 28.5%. These findings indicate that the effectiveness of productive zakat programs can be enhanced when accompanied by more intensive and continuous mentoring. The study provides practical implications for zakat management institutions to strengthen the mentoring aspect in their economic empowerment programs.